Circulating phospholipid patterns in NAFLD patients associated with a combination of metabolic risk factors - Tiwari-Heckler, Shilpa; Gan-Schreier, Hongying; Stremmel, Wolfgang; Chamulitrat, Walee; Pathil-Warth, Anita (Nutrients, 2018)
Background: Non-alcoholic fatty liver disease (NAFLD) is associated with inefficient macro- and micronutrient metabolism, and alteration of circulating phospholipid compositions defines the signature of NAFLD. This current study aimed to assess the pattern of serum phospholipids in the spectrum of NAFLD, and its related comorbidities and genetic modifications. Methods: 97 patients with diagnosed NAFLD were recruited at a single center during 2013–2016. Based on histological and transient elastography assessment, 69 patients were divided into non-alcoholic steatohepatitis (NASH) and non-alcoholic fatty liver (NAFL) subgroups. 28 patients served as healthy controls. Serum phospholipids were determined by liquid-chromatography mass spectrometry (LC-MS/MS). Results: The total content of phosphatidylcholine (PC) and sphingomyelin in the serum was significantly increased in NAFL and NASH patients, compared to healthy controls. In addition, serum lysophospatidylethanolamine levels were significantly decreased in NAFL and NASH individuals. Circulating PC species, containing linoleic and α-linolenic acids, were markedly increased in NAFLD patients with hypertension, compared to NAFLD patients without hypertension. The pattern of phospholipids did not differ between NAFLD patients with diabetes and those without diabetes. However, NAFLD patients with hyperglycemia (blood glucose level (BGL) >100 mg/dL) exhibited significantly a higher amount of monounsaturated phosphatidylethanolamine than those with low blood glucose levels. In addition, NAFLD patients with proven GG-genotype of PNPLA3, who were at higher risk for the development of progressive disease with fibrosis, showed lower levels of circulating plasmalogens, especially 16:0, compared to those with CC- and CG-allele. Conclusions: Our extended lipidomic study presents a unique metabolic profile of circulating phospholipids associated with the presence of metabolic risk factors or the genetic background of NAFLD patients.
Gesehen am 11.09.2018